The Effect of Giving Young Coconut Water on Lowering Blood Pressure in Elderly People with Hypertension in Sarirahayu Hamlet, Cimaragas Health Center Working Area - Fitriani, Tia; Yuningsih, Aneng; Khaeriyah, Yayi Siti (KIAN JOURNAL, 2023)
Hypertension is a cardiovascular disorder, hypertension is the number 1 cause of death in the world and it is estimated that hypertension will continue to increase. According to WHO, the blood pressure limit that is still considered normal is 140/90 mmHg while blood pressure ≥160/95 mmHg is declared hypertension. This study aims to determine the effect of giving young coconut water on lowering blood pressure in the elderly with hypertension in Sarirahayu Hamlet, Cimaragas Health Center Working Area. The type of research used is quantitative using Quasy Experiment with one group pretest-postest design. The population in this study were 38 respondents, with the sampling technique using purposive sampling technique. The sample of this study amounted to 15 respondents, namely elderly people with hypertension. The results of this study indicate that after being given young coconut water to 15 respondents, all respondents experienced a decrease in blood pressure. Based on the results of the Wilcoxon test, the p value = 0.001 < α = 0.05, which means that there is an effect of giving young coconut water on lowering blood pressure in the elderly with hypertension in Sarirahayu Hamlet, Cimaragas Health Center Working Area.